2002
DOI: 10.5144/0256-4947.2002.252
|View full text |Cite
|
Sign up to set email alerts
|

Hypergastrinemia and H. Pylori Infection as a Risk Factor for Colorectal Cancer

Abstract: AS Al-Mulhim, H Al Hosieny Mohammad, Hypergastrinemia and H. Pylori Infection as a Risk Factor forColorectal Cancer. 2002; 22(3-4): 252-255 Several lines of evidence support an etiological role for gastrin in colon cancer carcinogenesis. The hormone exerts trophic effects on the mucosa of gastrointestinal tract including that of the colon.1 Gastrin has also been shown to be mitogenic for colonic cancer cells in vitro, and stimulate growth of experimental colonic tumors in rodents.3,4 These trophic effects c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…22,23 There are recent reports illuminating that an elevated gastrin level promotes CRA tumorigenesis, which could also be seen in our multivariate logistic regression model analysis. 24,25 Considering that Hp stimulates gastrin expression, and that both Hp and gastrin exert the carcinogenic effect of CRA, we therefore hypothesized that Hp might stimulate gastrin expression and then promote tumor progression in CRA patients. However, because the relevant information is still limited, we compared the serum gastrin expression and inter-tumor ki-67 (a well-known biomarker for cancer cell proliferation) expression between Hp + CagA + /Hp + C agA − patients and Hp − patients, and the results disclosed that both of them were increased in Hp + CagA + patients and Hp + CagA − patients compared to Hp − patients, suggesting that Hp might promote CRA progression by advocating gastrin expression, which might be caused by Hp-induced atrophy changes of the gastric body mucosa, leading to increased levels of serum gastrin by negative feedback on antral G cells, and subsequently stimulated tumor cell proliferation of CRA, which caused an elevated ki-67 expression.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 There are recent reports illuminating that an elevated gastrin level promotes CRA tumorigenesis, which could also be seen in our multivariate logistic regression model analysis. 24,25 Considering that Hp stimulates gastrin expression, and that both Hp and gastrin exert the carcinogenic effect of CRA, we therefore hypothesized that Hp might stimulate gastrin expression and then promote tumor progression in CRA patients. However, because the relevant information is still limited, we compared the serum gastrin expression and inter-tumor ki-67 (a well-known biomarker for cancer cell proliferation) expression between Hp + CagA + /Hp + C agA − patients and Hp − patients, and the results disclosed that both of them were increased in Hp + CagA + patients and Hp + CagA − patients compared to Hp − patients, suggesting that Hp might promote CRA progression by advocating gastrin expression, which might be caused by Hp-induced atrophy changes of the gastric body mucosa, leading to increased levels of serum gastrin by negative feedback on antral G cells, and subsequently stimulated tumor cell proliferation of CRA, which caused an elevated ki-67 expression.…”
Section: Discussionmentioning
confidence: 99%
“…This integrative model also helps explain the interest in H. pylori's potential role in carcinogenesis of non-gastric malignancies. Furthermore, studies have shown its associated risk with non-Hodgkin's lymphoma, pancreatic cancer, colorectal cancer, and even lung cancer with varied responses [20][21][22][23].…”
Section: H Pylori Infection and Gastric Cancermentioning
confidence: 99%